A call for caution in the analysis of lipids and other small biomolecules from archaeological contexts. (August 2021) - Whelton, Helen L.; Hammann, Simon; Cramp, Lucy J.E.; Dunne, Julie; Roffet-Salque, Mélanie; Evershed, Richard P.
Abstract: The analysis of lipids and other biomolecules preserved in archaeological artefacts, using chromatographic and mass spectrometric techniques, is a powerful approach, which has provided unprecedented insights into the diet and cultural practices of past populations. In more recent years, the now-mature field of organic residue analysis (ORA) has entered a new phase, undertaking large scale analyses and providing broader perspectives on the uses of pottery over a range of both temporal and spatial scales. However, it has become apparent from the literature that there are significant pitfalls in applying the technique, often due to inexperience or lack of knowledge, that can lead to the production of data which is essentially worthless, because it either lacks analytical rigour or a valid archaeological interpretation. This is partly because ORA sits between chemistry and archaeology and projects are sometimes conducted by researchers not sufficiently familiar in the respective other discipline. Consequently, there have been numerous examples in recent years that showed a lack of understanding of critical points in ORA. This has two serious consequences: 1. the often-wide perpetuation of false knowledge, and 2. the use of a method that is both costly and destructive of irreplaceable archaeological material, which is not compensated for with useful information-gain. Here, we address some common errors encountered either in published literature or during peer-review and discuss the most important errors and misconceptions around ORA. In particular, we discuss use of unsuitable biomarkers, contamination, poor analytical data quality, the limitations of gas chromatography (GC), GC-mass spectrometry (GC-MS) and MS databases, and problems with the interpretation of ORA data. Here, we offer best practice advice and we hope that this will help, and encourage, all researchers looking to apply ORA in their studies, as we are optimistic that these pitfalls can be avoided, and the quality of published research consequently raised. Highlights: Organic Residue Analysis (ORA) of lipids is widely used in archaeological science. Common misconceptions and pitfalls in applying of ORA are discussed. Issues discussed include the incorrect use of biomarkers and analytical techniques. Best practice advice is offered to ensure high quality of studies using ORA.